The Effect of Resiprocal Teaching Learning on Critical Thinking Ability - Romy Faisal Mustofa; Fitri Sucianti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
This study aims to determine the effect of reciprocal teaching-learning on students' critical thinking in the body's immune system material in class XI IPA SMA Cintawana Islamic Boarding School, Tasikmalaya. This is a quantitative study of quasi-experimental models with a pre-test post-test control group design. The population were all students of class XI IPA SMA Cintawana Islamic Boarding School, Tasikmalaya, with a total of 50 students. Samples were taken using total sampling technique consisting of class XI IPA 2 as many as 25 students as the experimental class and class XI IPA 1 as many as 25 students as the control class. The instrument used was a critical thinking ability test in the form of a description consisting of 15 items in the body's immune system material. The data analysis technique used the t test with ? = 0.05. Based on the results of research and data analysis, it can be concluded that there was the effect of reciprocal teaching-learning on critical thinking skills of XI IPA high school students at the Cintawana Islamic Boarding School in Tasikmalaya on the body's immune system material.